2021
DOI: 10.4081/hr.2021.8857
|View full text |Cite
|
Sign up to set email alerts
|

Heparin-Induced Thrombocytopenia and COVID-19

Abstract: Heparin-induced thrombocytopenia (HIT) has not been included as a possible cause of thrombocytopenia in Coronavirus Disease 2019 (COVID-19) patients. We report a case of HIT in a patient with COVID-19 treated with heparin. A 78-yearold man was admitted to our hospital for acute respiratory failure and acute renal failure due to SARS-CoV-2 infection; in intensive care unit, one 5000IU heparin dose (day 0, platelet count 305000/μL). On day 2, haemoglobin started to decrease and heparin was stopped. On day 10, pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 18 publications
0
13
0
1
Order By: Relevance
“…Considering that one of the main characteristics of COVID-19 is hypercoagulability, and therefore the increased risk of venous and arterial thrombosis, it is necessary to differentiate from Heparin-induced thrombocytopenia (HIT) [ 67 , 68 , 69 ], particularly secondary to the use of vaccines [ 70 ]. Uaprasert et al [ 71 ], in a systematic review and meta-analysis, found a pooled incidence of HIT of 0.8%, being slightly higher in critically ill COVID-19 patients.…”
Section: Introductionmentioning
confidence: 99%
“…Considering that one of the main characteristics of COVID-19 is hypercoagulability, and therefore the increased risk of venous and arterial thrombosis, it is necessary to differentiate from Heparin-induced thrombocytopenia (HIT) [ 67 , 68 , 69 ], particularly secondary to the use of vaccines [ 70 ]. Uaprasert et al [ 71 ], in a systematic review and meta-analysis, found a pooled incidence of HIT of 0.8%, being slightly higher in critically ill COVID-19 patients.…”
Section: Introductionmentioning
confidence: 99%
“…As anticoagulants have been used for both treatment and prevention during COVID-19 especially in advanced illnesses, it is not surprising that eventually there would emerge uncommon citations of heparin-induced thrombocytopenias [76][77][78][79][80][81][82][83][84][85][86][87][88]. Most of the latter, although not all, have been associated with LAC lupus anticoagulant, anti-CL anticardiolipin, anti-ß2 anti-ß2-glycoprotein-I,…”
Section: Heparin-induced Thrombocytopenia During Covid-19mentioning
confidence: 99%
“…Antibody-mediated mechanisms involving engagement of the FcγRIIA receptor on platelets were also shown to contribute to procoagulant activity in severe COVID-19 [ 13 , 14 ]. Although the antigenic specificity of these antibodies could not always be defined, antibodies to PF4 were shown to be involved in certain cases [ 15 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Antibody-mediated mechanisms involving engagement of the FcγRIIA receptor on platelets were also shown to contribute to procoagulant activity in severe COVID-19 [13,14]. Although the antigenic specificity of these antibodies could not always be defined, antibodies to PF4 were shown to be involved in certain AU : Anabbreviationlisthasbeencompiledforthoseusedthroughoutth cases [15][16][17][18][19][20][21][22]. PF4, also called CXCL4, is a tetrameric chemokine stored in platelet alpha-granules [23].…”
mentioning
confidence: 99%